KEMANDIRIAN ANAK USIA DINI DALAM MENGHADAPI SEPARATION ANXIETY DI TK SAKINAH 1 CIBADAK - Januarti, Hani; Sari, Nurlaela; Putri Nabila, Aulia; Pratiwi, Anisa; Purnama Sari, Leli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the occurrence of separation anxiety among young children when they first enter the school environment, which often affects their level of independence in daily activities. This situation requires the active involvement of both teachers and parents to support children’s adaptation. The purpose of this research is to describe the level of independence of early childhood in dealing with separation anxiety at TK Sakinah 1 Cibadak. This study applies a qualitative method with a descriptive approach. The participants include children, teachers, and parents. Data were collected through observation, interviews, and documentation. The analysis process involves data reduction, data display, and drawing conclusions. The findings reveal that children’s independence varies depending on parenting patterns, emotional readiness, and instructional strategies applied by teachers. Children who demonstrate higher independence tend to adjust more easily and experience less anxiety during separation. Therefore, it can be concluded that independence plays a significant role in helping children cope with separation anxiety, highlighting the importance of collaboration between teachers and parents in fostering this ability.